Communicative Language Teaching in Selected Students: Basis for Pro-posed Use of Task Based Learning Approach in Developing Speaking Skills - Maming, Jimmy Bernabe; Llena, Annalyn Cristobal; Maravilla, Wes Harven G. (Future Science / FSH-PH Publications, 2022)
This study employed communicative language education to assist a subset of a public school in Tondo, Manila, Philippines, especially the Junior High School Grade 7 students, in improving their English-speaking abilities. The researchers used the Direct Teaching Method to conduct a teaching and learning process (Pre-test). The students were then given a speaking test. Following the pre-test, the researchers started the teaching-learning process by teaching Communicative Language. After two months of using the communicative language education strategy, the researcher repeated the speaking test (post-test). Compiling the data and calculating the speaking test scores. The following statistical instruments were applied to the data collected for analysis and interpretation: t-Test: Two-Sample Assuming Equal Variances, Weighted Mean, Frequency and Percent Distribution, Standard Deviation, One-Way ANOVA [Single Factor], and the findings of the pre-test and post-test show a considerable improvement in the selected students' speaking ability. Task-based learning is excellent for cultivating language ability because it allows students to participate in natural conversation. The task-based approach gives learners a natural setting in which to utilize language. There are several opportunities for interaction while students try to finish an assignment. Such engagement is said to help with language development since it forces students to converse with one another and articulate their meaning.